Practicality and Effectiveness of Biology Modules Based on Local Potential in Enrekang Regency - Hasmiati, Hasmiati; Rukmana, Musma; Agustina, Tika Putri; Watung, Fernando (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2024)
The purpose of this study is to explain the practicality and effectiveness of the local potential-based Biology module that has been previously developed by researchers through research and development (RD). Â This study uses a one-shot case study design as a pre-experiment. Product trials were conducted in one class selected by purposive sampling with 28 participants. Â The instrument used in this study was a questionnaire sheet for the responses of educators and students to measure the practicality of the module. learning outcomes test instrument was also used to measure the module's effectiveness. The analysis's findings educator's response obtained a percentage value of 100% and 92% for the response of students. At the same time, students' learning outcomes reached an average of 89.8. Â These findings provide a conclusion that the biology module based on local potential is practical to use and can effectively improve student learning outcomes.